2023
DOI: 10.3389/fmicb.2023.1220670
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of mechanism of high quality and yield of Gastrodia elata Bl. f. glauca by the isolation, identification, and evaluation of Mycena

En Yu,
Qun Liu,
Yugang Gao
et al.

Abstract: Gastrodia elata Bl. f. glauca is an important traditional Chinese medicinal plant. The yield and quality of Gastrodia elata Bl. have significantly decreased due to multigenerational asexual reproduction. Therefore, it is necessary to have sexual reproduction of Gastrodia elata Bl. to supplement the market supply. Seeds of G. elata Bl. have no endosperm, and their sexual reproduction depends on the nutrients provided by the embryo cells infected by Mycena fungi to complete seed germination. However, Mycena fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Mortierella rishikesha maintained highest relative abundance (>9%) in the rhizosphere throughout the growth stages of G. elata , indicating that it might be a core fungal species under greenhouse conditions. A high relative abundance of Mortierella has also been observed in the fungal communities of G. elata by Wang et al (2023) and Yu et al (2023) . Mortierella species in agricultural soils, the rhizosphere, and vegetable tissues are plant growth-promoting fungi ( Ozimek and Hanaka, 2020 ).…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Mortierella rishikesha maintained highest relative abundance (>9%) in the rhizosphere throughout the growth stages of G. elata , indicating that it might be a core fungal species under greenhouse conditions. A high relative abundance of Mortierella has also been observed in the fungal communities of G. elata by Wang et al (2023) and Yu et al (2023) . Mortierella species in agricultural soils, the rhizosphere, and vegetable tissues are plant growth-promoting fungi ( Ozimek and Hanaka, 2020 ).…”
Section: Discussionmentioning
confidence: 78%
“…In this study, we found that Proteobacteria was the predominant phylum in the rhizosphere of G. elata , followed by Acidobacteria, which corresponds to the bacterial communities in the cropping soil of G. elata ( Yuan et al, 2020 ) and in the surrounding soil of G. elata protocorms ( Yu et al, 2023 ). Yu et al (2023) reported that Proteobacteria showed a positive relationship with soil ammonium nitrogen content in the soil surrounding G. elata.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations